FCGR2A and FCGR3A polymorphisms and clinical outcome in metastatic colorectal cancer patients treated with first-line 5-fluorouracil/folinic acid and oxaliplatin +/- cetuximab - Kjersem, Janne B (BioMed Central, 2014)
BACKGROUND: Polymorphisms of genes encoding the Fcy receptors (Fc fragment of IgG receptor 2A (FCGR2A) and 3A (FCGR3A)), which influence their affinity for the Fc fragment, have been linked to the pharmacodynamics of monoclonal antibodies. Most studies have been limited by small samples sizes and have reported inconsistent associations between the FCGR2A and the FCGR3A polymorphisms and clinical outcome in metastatic colorectal cancer (mCRC) patients treated with cetuximab. We investigated the association of these polymorphisms and clinical outcome in a large cohort of mCRC patients treated with first-line 5-fluorouracil/folinic acid and oxaliplatin (Nordic FLOX) +/- cetuximab in the NORDIC-VII study (NCT00145314). METHODS: 504 and 497 mCRC patients were evaluable for the FCGR2A and FCGR3A genotyping, respectively. Genotyping was performed on TaqMan ABI HT 7900 (Applied Biosystems, Foster City, CA, USA) with pre-designed SNP genotyping assays for FCGR2A (rs1801274) and FCGR3A (rs396991). RESULTS: The response rate for patients with the FCGR2A R/R genotype was significantly increased when cetuximab was added to Nordic FLOX (31% versus 53%, interaction P = 0.03), but was not significantly different compared to the response rate of patients with the FCGR2A H/H or H/R genotypes given the same treatment. A larger increase in response rate with the addition of cetuximab to Nordic FLOX in patients with KRAS mutated tumors and the FCGR2A R/R genotype was observed (19% versus 50%, interaction P = 0.04). None of the FCGR3A polymorphisms were associated with altered response when cetuximab was added to Nordic FLOX (interaction P = 0.63). Neither of the FCGR polymorphisms showed any significant associations with progression-free survival or overall survival. CONCLUSION: Patients with KRAS mutated tumors and the FCGR2A R/R polymorphism responded poorly when treated with chemotherapy only, and experienced the most benefit of the addition of cetuximab in terms of response rate.